Sedimentary environment evolution of the Jialingjiang Formation in the Maling area: Evidence from sedimentology and major and trace elements - Liuyun Ouyang; Qi He; Kun Liu; Wei Yang; Kainan Mao (地质科技通报, 2022)
The Maling area is located in Xingyi City, Guizhou Province.It is an idea area to study the evolution of the sedimentary environment in the Early Triassic for its sedimentary strata saddle the Permian and Triassic transition.Based on the integrations of field survey of the Jialingjiang Formation in this area, measured profile data, microscopic observation in the laboratory, and 14 major and trace elements, the evolution of its depositional environment was discussed.Carbonate rocks and clastic rocks are mainly exposed in Maling area, which can be divided into four members.A total of 16 rock samples were collected for analysis.Combined with sedimentary facies, palaeoclimate index (SiO2/Al2O3 ratio), paleosalinity index, paleobathymetric index (CaO/MgO and Sr/B aratio), the following changes are identified in the Early Triassic: ① The abnormally hot and dry climate gradually transitioned to an overall humid climate, which may be the result of the Early Triassic and the biological recovery provided suitable climatic conditions; ②The alternation of shallow sea and deep sea occurred. The first to fourth members of the Jialingjiang Formation are dominated by open platform facies, tidal flat facies, open-limited-open platform facies, and limited platform facies, respectively. The local appearance of bioclasts such as bivalves confirms that the Early Triassic marine environment in this area was abnormally variable and had multiple stages of deterioration-improvement evolution.